2007
DOI: 10.1007/s10955-007-9387-9
|View full text |Cite
|
Sign up to set email alerts
|

A Topological Glass

Abstract: We propose and study a model with glassy behavior. The state space of the model is given by all triangulations of a sphere with $n$ nodes, half of which are red and half are blue. Red nodes want to have 5 neighbors while blue ones want 7. Energies of nodes with different numbers of neighbors are supposed to be positive. The dynamics is that of flipping the diagonal of two adjacent triangles, with a temperature dependent probability. We show that this system has an approach to a steady state which is exponentia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 19 publications
(19 reference statements)
1
30
0
Order By: Relevance
“…This dynamics can explore networks embedded in surfaces of different genus, and displays a dynamical slowing down as a function of the inverse temperature of the Monte Carlo algorithm. Therefore in these simulations the ground state, ordered network is not observed, similarly to what has been observed in models of glass and foam dynamics [88,89]. This approach is very different from the one proposed in the present article, although the focus is always the characterization of the network geometry.…”
Section: Relation To Triangulations Foams and Planar Graphsmentioning
confidence: 60%
See 2 more Smart Citations
“…This dynamics can explore networks embedded in surfaces of different genus, and displays a dynamical slowing down as a function of the inverse temperature of the Monte Carlo algorithm. Therefore in these simulations the ground state, ordered network is not observed, similarly to what has been observed in models of glass and foam dynamics [88,89]. This approach is very different from the one proposed in the present article, although the focus is always the characterization of the network geometry.…”
Section: Relation To Triangulations Foams and Planar Graphsmentioning
confidence: 60%
“…This approach is very different from the one proposed in the present article, although the focus is always the characterization of the network geometry. For example the phase transitions present in the Quantum Complex Network Geometries are very different from the one observed in [29,88,89]. In fact in the Complex Quantum Network Geometries the observed phase transitions are non-equilibrium phase transitions, they are determined by the quenched disorder in the network.…”
Section: Relation To Triangulations Foams and Planar Graphsmentioning
confidence: 79%
See 1 more Smart Citation
“…At very low temperatures (β → ∞), the probability allows only moves that lower the energy or leave it unchanged, driving therefore the system towards the ground state where all vertices have degree equal to k (if it is an integer number). However, it was observed that, for low genus embeddings, a 'freezing' transition takes place and the system cannot reach its ground state in any finite time [9,22,23]. The general cases with arbitrary genus g have not been studied yet, and this is indeed the topic of the present paper.…”
Section: Statistical Physics Of Embedded Triangulationsmentioning
confidence: 92%
“…The appealing aspect of such a topological glass is that the typical features of structural glasses are observed in a simple triangulation of a surface [9]. It has been shown that this model has some of the typical properties of a strong glass with aging behaviour, but without breakdown of the fluctuation-dissipation relation [9,[20][21][22][23] . In this paper, we extend the topological glass model, originally developed in [9], to the general case of triangulations embedded on complex surfaces with different genus.…”
Section: Random and Frozen States In Complex Triangulationsmentioning
confidence: 99%